2008
DOI: 10.1007/s11274-008-9800-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of heavy metals by the exopolysaccharide produced by Paenibacillus jamilae

Abstract: The biosorption of several toxic heavy metals (Pb, Cd, Co, Ni, Zn and Cu) by the exopolysaccharide (EPS) produced by Paenibacillus jamilae, a potential biosorbent for metal remediation and recovery was studied. Firstly, the biochemical composition of this bacterial polymer was determined. Glucose was the most abundant neutral sugar, followed by galactose, rhamnose, fucose and mannose. The polymer presented a high content of uronic acids (28.29%), which may serve as binding sites for divalent cations. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(49 citation statements)
references
References 29 publications
0
48
1
Order By: Relevance
“…This study demonstrates that EPS could represent a fraction of the organic ligands interacting with Fe, thus improving our knowledge on the possible nature of organic ligands controlling Fe biogeochemistry. Given that EPS could precipitate in presence of high Fe concentrations (Morillo Pérez et al, 2008), the formation of a much stronger Fe-EPS association following 9 weeks versus 24 h pre-equilibration, could result from conformational changes.…”
Section: Role Of Eps On Fe Biogeochemistrymentioning
confidence: 99%
“…This study demonstrates that EPS could represent a fraction of the organic ligands interacting with Fe, thus improving our knowledge on the possible nature of organic ligands controlling Fe biogeochemistry. Given that EPS could precipitate in presence of high Fe concentrations (Morillo Pérez et al, 2008), the formation of a much stronger Fe-EPS association following 9 weeks versus 24 h pre-equilibration, could result from conformational changes.…”
Section: Role Of Eps On Fe Biogeochemistrymentioning
confidence: 99%
“…In addition, EPS produced by both PNSB strains was more efficient at adsorb all HMs tested in the presence of 3% NaCl when compared with other previous studies. These had shown that their EPS had a high affinity for Pb but a low affinity for Cd, Co, Cu, Ni and Zn (Iyer et al 2005;Morillo Perez et al 2008). This is most likely due to differences in their chemical composition, which has not been investigated.…”
Section: Removal Of Heavy Metals By Exopolymeric Substances and Pnsb mentioning
confidence: 99%
“…An inhibitory effect was observed on growth and EPS production when TPOMW concentration was increased (Morillo et al 2006). This EPS produced by P. jamilae through fermentation of OMWs has been investigated in relation to its potential application as a biofilter of heavy-metal-contaminated water (Morillo et al 2008b).…”
Section: Biopolymers and Enzymesmentioning
confidence: 99%